Comparison of clinical and laboratory characteristics during two major paediatric meningitis outbreaks of echovirus 30 and other non-polio enteroviruses in Germany in 2008 and 2013 - Rudolph, Henriette; Prieto Dernbach, Roberto; Weiß, Christel; Schroten, Horst; Tenenbaum, Tobias (European journal of clinical microbiology & infectious diseases, 2017)
Viral meningitis is mainly caused by non-polio enteroviruses (NPEV). Large-scale data on the clinical characteristics between different outbreaks within the same region are lacking. This study aimed to analyse a possible influence of the circulating NPEV genotype on the disease outcome of affected children. A retrospective cohort study analysing two major outbreaks of NPEV meningitis in Germany in 2008 and 2013 was conducted in cooperation with the National Reference Centre for Poliomyelitis and Enteroviruses (NRC PE) and five German children’s hospitals. A total of 196 patients with laboratory-confirmed NPEV meningitis were enrolled. In 2008, children with NPEV meningitis had significantly higher fever and showed more behavioural changes and less back pain. To better define typical findings in echovirus 30 (E-30) meningitis, patients were split into the following three groups: E-30 positive patients, patients with “Non E-30” infection and patients with “Untyped” NPEV infection. E-30 positive patients were significantly older and their disease course was more acute, with early admission to but also early discharge from hospital. E-30 positive patients showed a significantly higher rate of headache and meningism, and a lower rate of diarrhoea and clinically defined septicaemia when compared to the others. Regarding laboratory testing, E-30 positive patients presented with significantly elevated peripheral blood neutrophil counts when compared to patients with “Non E-30” or “Untyped” NPEV infection. In conclusion, E-30 meningitis in children shows a characteristic pattern of clinical features. To further characterise NPEV strains worldwide, continuous surveillance and typing of NPEV strains causing central nervous system disease is warranted.